2015
DOI: 10.1007/978-3-319-19593-3_2
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Business Model Experimentation and Technical Debt

Abstract: Abstract. The use of lean software development methodology and business model experimentation has become popular in software companies in recent years. Business model experimentation is used to validate assumptions made on a product from real customers before the actual product is created. A minimum viable product is used to test the business model by gathering and measuring customer feedback. However, in many cases creating a minimum viable product requires the development team to take shortcuts and workaroun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Three primary studies that have identified software engineering management are [73,56,74]. However, these papers primarily focus on software engineering processes [73,56] and software quality [74].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Three primary studies that have identified software engineering management are [73,56,74]. However, these papers primarily focus on software engineering processes [73,56] and software quality [74].…”
Section: Discussionmentioning
confidence: 99%
“…Three primary studies that have identified software engineering management are [73,56,74]. However, these papers primarily focus on software engineering processes [73,56] and software quality [74]. Although the Hunter-gatherer cycle presented by Nguyen-Duc et al [56] presents how startups can handle the https://doi.org/10.1016/j.jss.2018.06.043 dynamic evolution of product-market fit, which is part of both business experimentation and customer development, it is primarily focused towards software engineering processes in startups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yli-Huumo et al [19] study the relationship between business model experimentation and TD, in order to explore if conducting the business model experimentation impacts the amount of TD incurred. The business model experimentation is a technique used to validate assumptions made about a product with real customers, before creating the actual product.…”
Section: Technical Debt In Software Startupsmentioning
confidence: 99%
“…The literature of corporate entrepreneurship shows that to generate revenue streams and values for shareholders, large companies are engaged in either internal startup (or internal corporate venture [30]) or external startup (or external corporate venture) [31], or both. external startup usually includes joint venturing (e.g.…”
Section: Internal Startupmentioning
confidence: 99%